Analisis Belenggu Feminisme dalam Cerpen Tio Na Tonggi Karya Hasan Al-Banna dengan Teori Feminisme Marxis: Karl Marx - David Afrianus Pasaribu; Elvira Eninta Ginting; Tessa Anastasia Farasi (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research analyzes the short story Tio Na Tonggi by Hasan Al-Banna using Marxist Feminism theory to reveal gender injustice and oppression of women in a patriarchal society. Through descriptive methods and a qualitative approach, this research highlights how the main character, Tio, is trapped in social and economic norms that place him in a subordinate position. In this short story, women are represented as objects of sacrifice who depend on the family, with the character Pitta Bargot Nauli as a symbol of women's sacrifice for the benefit of the family, even though their rights and freedoms are neglected. Apart from that, Tio's oppression is also seen through social expectations and economic dependence that bind her to traditional roles, as well as the exploitation of women's bodies as economic resources in the capitalist system. The research results show that this short story depicts how patriarchal and capitalist structures contribute to the marginalization and oppression of women, both in the social, economic and family realms.